Practical methods for analysis and design of HV installation grounding systems - Popovic, Ljubivoje M. (London : Academic Press, 2018)
Practical Methods for Analysis and Design of HV Installation Grounding Systems gives readers a basic understanding of the modeling characteristics of the major components of a complex grounding system. One by one, the author develops and analyzes each component as a standalone element, but then puts them together, considering their mutual disposition, or so-called proximity effect. This is the first book to enable the making and analysis of the most complex grounding systems that are typical for HV substations located in urban areas that uses relatively simple mathematical operations instead of modern computers. Since the presented methods enable problem-solving for more complex issues than the ones solved using National, IEC and/or IEEE standards, this book can be considered as an appendix to these standards.
3.2.5 Conductor Substituting All Surrounding Neutral Conductors3.2.6 Application of the Presented Method; 3.3 GROUND FAULT CURRENT DISTRIBUTION FOR A FAULT AT ANY PLACE ALONG A CABLE LINE; 3.3.1 Feeding Cable Line With Only One Metal Sheath; 3.3.2 Feeding Cable Line Having Three Single-Core Cables; 3.4 QUANTITATIVE ANALYSIS; 3.4.1 Calculated Reduction Factor; 3.4.2 Actual Reduction Factor; 3.4.3 Critical Currents Through the Sheaths of a Cable Line; 3.4.4 General Observations; REFERENCES; FURTHER READING; 4 -- Different Cases of Nonhomogeneous Feeding Lines
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed February 28, 2018).
Keywords: Electric currents -- Grounding; Electric transformers -- Installation; High voltages -- Installation; TECHNOLOGY & ENGINEERING / Mechanical; Electronic books